Analysis of the influence of service quality on patient satisfaction in obstetrics and gynecology at the Harapan Kasih Main Clinic in Ngabang Landak Regency - Gusti Rafli; Samsuddin Samsuddin (Electronic Journal of Education, Social Economics and Technology, 2025)
This study examines the impact of quality service on the patient satisfaction at Utama Harapan Kasih Clinic. The study highlights the importance of service in achieving satisfaction. The study aims to analyze this relationship quantitatively using an associative approach. Data collection was carried out through questionnaires distributed to 100 respondents, supplemented by secondary data related to patient volume and clinic revenue. Sampling used saturated sampling technique. This study used simple linear regression analysis, supported by classical assumption tests such as validity, reliability, normality test. The results showed a positive relationship between service quality and patient satisfaction. Simultaneous testing showed that variables significantly influenced patient satisfaction. The R-square value of 69.9% indicates that other factors contributed 31.1% to patients satisfaction. This study underlines the importance of increase service quality to increase patient satisfaction offering insights to improve clinic revenue.